Quantification of Brain β-Amyloid Load in Parkinson's Disease With Mild Cognitive Impairment: A PET/MRI Study - Garon, Michela; Weis, Luca; Fiorenzato, Eleonora; Pistonesi, Francesca; Cagnin, Annachiara; Bertoldo, Alessandra; Anglani, Mariagiulia; Cecchin, Diego; Antonini, Angelo; Biundo, Roberta (Frontiers in Neurology, 2022)
Background: Mild cognitive impairment in Parkinson’s disease (PD-MCI) is associated with faster cognitive decline and conversion to dementia. There is uncertainty about the role of β-amyloid co-pathology and its contribution to the variability in PD-MCI profile and cognitive progression. Objective: To study how presence of β-amyloid (Aβ) affects clinical and cognitive manifestations as well as regional brain volumes in PD-MCI. Methods: Twenty-five PD-MCI patients underwent simultaneous PET/3T-MRI with [18F]flutemetamol and a clinical and neuropsychological examination allowing level II diagnosis. We tested pairwise differences in motor, clinical and cognitive features with Mann–Whitney U test. We calculated [18F]flutemetamol standardized uptake value ratios (SUVR) in striatal and cortical ROIs, and performed a univariate linear regression analysis between the affected cognitive domains and the mean SUVR. Finally, we investigated differences in cortical and subcortical brain regional volumes with MRI. Results: There were 8 Aβ+ and 17 Aβ- PD-MCI. They did not differ for age, disease duration, clinical, motor, behavioral and global cognition scores. PD-MCI-Aβ+ showed worse performance in the overall executive domain (p=0.037). Subcortical ROIs analysis showed significant β-amyloid deposition in PD-MCI-Aβ+ patients in the right caudal and rostral middle frontal cortex, in precuneus, in left paracentral and pars triangularis (p<0.0001) and bilaterally in the putamen (p=0.038). Cortical regions with higher amyloid load correlated with worse executive performances (p<0.05). VBM analyses showed no between groups differences. Conclusions: Presence of cerebral β-amyloid worsens executive functions, but not motor and global cognitive abilities in PD-MCI and it is not associated with middle-temporal cortex atrophy. These findings, together with the observation of significant proportion of PD-MCI-Aβ-, suggest that β-amyloid may not be the main pathogenetic determinant of cognitive deterioration in PD-MCI, but it would rather aggravate deficits in domains vulnerable to Parkinson primary pathology.